AN IMPLEMENTATION OF CHILD CUSTODY DECISION AFTER DIVORCE: A STUDY IN MONDOLUKU VILLAGE, WRINGINANOM, GRESIK - Suhessyani, Anggrita Esthi; Permanasari, Lolita; Munawaroh, Siti; Saraswati, Arya Made Sridevi (YURIS: Journal of Court and Justice, 2024)
Marriage is an internal bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family. However, domestic harmony requires sustained effort and mental and material preparations. When conflicts in marriage are not resolved, divorce is often an option. This research aims to understand the practice of implementing decisions related to child custody after divorce in Mondoluku Village, Wringinanom, Gresik. The method used is qualitative with data collection techniques through interviews, observations, and document studies. The results showed that many divorced couples do not implement court decisions related to child custody, which has a negative impact on children’s welfare. The obstacles involved a lack of understanding of the law and economic constraints. Efforts from relevant parties, such as community leaders and local government agencies, in providing legal education and mediation have been implemented, but their effectiveness still needs to be improved. Therefore, this research is able to offer a comprehensive overview of child custody protection after divorce, which requires better coordination and increased resources to ensure children’s welfare. The research highlights that determining child custody involves various administrative and procedural steps, requiring cooperation among families, courts, and social institutions to prioritize the child’s best interests. It also points out challenges such as inadequate public understanding of custody, limited resources, and the psychological effects on children, which impact the effectiveness of custody implementation after divorce.